2019
DOI: 10.1038/s41386-019-0430-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of an NMDA receptor antagonist for reversing corticosteroid effects on the human hippocampus

Abstract: Preclinical and clinical research indicates that excess corticosteroid is associated with adverse effects on the hippocampus. Animal model data suggest that N-methyl-D-aspartate (NMDA) receptor antagonists may block corticosteroid effect on the hippocampus. This translational clinical trial investigated the effect of memantine vs. placebo on hippocampal subfield volume in humans receiving chronic corticosteroid therapy. Men and women (N = 46) receiving chronic prescription corticosteroid therapy were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(39 reference statements)
0
11
1
Order By: Relevance
“…Some of these effects were detected even after ten years of biochemical remission 22 23. Moreover, a few small studies have shown volumetric reductions in specific brain regions, including the hippocampus and amygdala,27–31 in patients using chronic and/or high-dose synthetic systemic glucocorticoids. Besides these structural abnormalities, several studies in animal models and patients with Cushing disease have also demonstrated widespread reductions in white matter integrity throughout the brain 32–36.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these effects were detected even after ten years of biochemical remission 22 23. Moreover, a few small studies have shown volumetric reductions in specific brain regions, including the hippocampus and amygdala,27–31 in patients using chronic and/or high-dose synthetic systemic glucocorticoids. Besides these structural abnormalities, several studies in animal models and patients with Cushing disease have also demonstrated widespread reductions in white matter integrity throughout the brain 32–36.…”
Section: Introductionmentioning
confidence: 99%
“…Rotator cuff tendon biopsies taken before and 7 weeks after glucocorticoid injection show a large increase in the proportion of cells positive for NMDA receptor subtype 1 staining that was not seen over the same period in response tendon repair surgery (36). These findings are supported by a recent study showing that 24-week NMDA receptor antagonist administration partly reversed the adverse effects of long-term glucocorticoid treatment on the CA3 region of the hippocampus (86). Together these studies indicate that glutamate and NMDA receptors are involved in tendinopathy and that glucocorticoid exposure both induces glutamate release and enhances stimulation of NMDA receptors leading to neuroexcitotoxic effects.…”
Section: Insulin Resistance and Type 2 Diabetesmentioning
confidence: 56%
“…This would rather require NMDA-R blockage with an antagonist parallel to MR stimulation. Interestingly, the NMDA-R antagonist memantine improved memory by inducing neurogenesis in mice [ 42 ], and reversed the adverse effects of long-term glucocorticoid administration on hippocampus volume in humans over a period of several months [ 43 ].…”
Section: Discussionmentioning
confidence: 99%